2019
DOI: 10.2166/wcc.2019.095
|View full text |Cite
|
Sign up to set email alerts
|

Future streamflow assessment in the Haihe River basin located in northern China using a regionalized variable infiltration capacity model based on 18 CMIP5 GCMs

Abstract: The impact of future climate change on streamflow is assessed in the Haihe River basin (HRB) by the Variable Infiltration Capacity (VIC) model, using the outputs from 18 general circulation models (GCMs) of the Coupled Model Inter-comparison Project Phase 5 (CMIP5). Three Representative Concentration Pathway (RCP) scenarios have been used, including RCP2.6, RCP4.5, and RCP8.5. Based on the model parameters calibration in six catchments in the HRB and parameter regionalization, the hydrological simulation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Research usually selects future climate scenarios and climate models or uses mathematical model calculations and downscaling methods to process the data and then analyzes the evolution of future climate and hydrology [11][12][13], while carrying out prediction and response research on hydrological elements [14,15]. Among them, the uncertain factors of future scenarios and hydrological models are the most difficult points in the research [16]. In recent years, the research on global climate models has made great progress.…”
Section: Introductionmentioning
confidence: 99%
“…Research usually selects future climate scenarios and climate models or uses mathematical model calculations and downscaling methods to process the data and then analyzes the evolution of future climate and hydrology [11][12][13], while carrying out prediction and response research on hydrological elements [14,15]. Among them, the uncertain factors of future scenarios and hydrological models are the most difficult points in the research [16]. In recent years, the research on global climate models has made great progress.…”
Section: Introductionmentioning
confidence: 99%
“…It is a mature and widely used method to predict future streamflow and water availability by using outputs from GCMs to drive regional hydrological models [36,37]. Bao et al [38] predicted the trend of streamflow in Hai River basin in the future by combining the variable infiltration capacity (VIC) model with climate outputs of CMIP5. The prediction showed that there might be an increasing trend for the streamflow and the increasing trend for streamflow in the north basin is higher than that in the south part.…”
Section: Introductionmentioning
confidence: 99%